Cationic porphyrinic photosensitizers in the inactivation of Candida albicans in blood - Sousa, Vera Catarina Ferreira de (2019)
Blood is an essential body fluid but is yet a source of microbial infections transmission. Consequently, the ability to disinfect blood and its derivatives has assumed great importance. Currently, the most used method for inactivating microorganisms, which can be only used in plasma or protein concentrates, is the combined use of a tri(n-butyl)phosphate and the detergent Tween 80. However, these chemicals must be removed after disinfection procedure once they are harmful to the membranes of erythrocytes and platelets of blood receptors. Antimicrobial Photodynamic Therapy (aPDT) has been suggested as an alternative technique to blood disinfection. Methylene blue (MB), psoralen and riboflavin are already approved photosensitizers (PS) in some countries to disinfect plasma/platelets, but there is no aPDT approved application for whole blood and erythrocytes concentrates. The aim of this study was to evaluate the effectiveness of aPDT to inactivate Candida albicans in blood, a microorganism frequently involved in bloodstream infections. For that, several cationic porphyrin derivatives were used to photoinactivate C. albicans in phosphate buffered saline (PBS), plasma and whole blood. Once MB is the mostly used PS to disinfect plasma, its efficacy was also evaluated for comparison. Samples and controls were exposed for 270 min to white light (380-700 nm) at an irradiance of 2.5 mW/cm2 and 150 mW/cm2 for PBS and whole blood/plasma, respectively. All the tested cationic porphyrin derivatives were effective to photoinactivate C. albicans in PBS. However, MB under the same conditions (concentration and light dose) did not appear to be efficient in C. albicans inactivation. In plasma, FORM and Tri-Py(+)-Me proved to be promising PSs in C. albicans photoinactivation. Although in whole blood the inactivation rates obtained with porphyrin derivatives were higher than the ones obtained with MB, further improvements are required. Nevertheless, the results indicate that aPDT using cationic porphyrinic photosensitizers seems to be a promising approach for the photoinactivation of C. albicans in plasma. Additionally, none of these PSs, in the tested concentrations in plasma and whole blood, had promoted significant hemolysis at the isotonic conditions when hemolysis was evaluated in whole blood and after the addition of aPDT treated plasma with these PSs to concentrated erythrocytes.